"My goal is to do the best that I can in this class": Relevance of potential‐based achievement goals for intrinsic motivation and course performance. (30th June 2021) - Daumiller, Martin; Zarrinabadi, Nourollah
Abstract : Goals are a core aspect of motivation. Elliot et al. (2015) introduced potential‐based goals as a type of self‐based goals that are conceptualised as seeking to do as well as one possibly could (potential approach goals) or seeking to avoid doing worse than one possibly could (potential avoidance goals). We follow up on this construct by examining its factorial structure and investigating its associations with intrinsic motivation and performance. We assessed 436 Iranian university students' potential‐based goals at the beginning of an English course, intrinsic motivation during the semester and end‐of‐course performance. Results attested factional separability similar to the original work, supporting generalisability concerning more collectivistic contexts. Potential approach goals were positively associated with intrinsic motivation and performance, while potential avoidance goals were negatively associated with performance, also after controlling for demographics. Overall, this affirms the relevance of potential‐based goals for a comprehensive understanding of how goals motivate individuals.